[PP.15.12] THE EFFECT OF PERINDOPRIL/AMLODIPINE FIXED-DOSE COMBINATION ON THE HEMODYNAMIC VARIABILITY IN HYPERTENSIVE PATIENTS WITH HIGH CARDIOVASCULAR RISK. (September 2016) - Nagy, V.; Wichmann, B.; Kender, Z.; Toth, M.
Abstract : Objective: The measured and calculated values of blood pressure (BP) recorded by ambulatory blood pressure monitoring (ABPM) [mean 24-hour BP, daytime BP, nighttime BP, diurnal pattern, BP variability visit by visit (standard deviation, coefficient of variation), vascular elasticity characterized by ambulatory arterial stiffness index (AASI)] are more appropriate predictors of long-term cardiovascular morbidity and mortality than office-based BP measurement. Design and method: The BP-reducing effect of the fix-dose combination perindopril/amlodipine (5 mg/5 mg, 5 mg/10 mg, 10 mg/5 mg, 10 mg/10 mg) was investigated in hypertensive patients with high cardiovascular risk from the ABPM subgroup of the large Hungarian trial, the PErindopril/Amlodipine Reduction of blood pressure Level study (PEARL). ABPM was performed in 262 patients (from 10335) (144 males, average age 60, 4 ± 11, 7 years) at the first- and at the 3-months visit. Data were presented as mean ± SD. For comparisons of BP measurements one sample t-test and Chi-square test were performed. A 2-sided α level of 0.05 was considered statistically significant. Results: The fixed combination perindopril/amlodipine reduced the mean office BP from 159.8/94.3 mmHg to 131.0/80.0 mmHg (p < 0.001) and the 24-hour BP from 146.1/84.3 mmHg to 127.6/75.9 mmHg (p < 0.001) in the ABPM subgroup. The diurnal pattern was not changed. The SD dropped from 15.3/11.4, to 10.5/8.9 (p < 0.01) and the CV from 10.5/13.5% to 8.2/11.7 % (p < 0.01). The AASI also decreased from 0.4571 ± 0.11 to 0.4168 ± 0.12 (p < 0.01). Conclusions: The results of our study show a significant and safety BP reduction in office as well as in ABPM in hypertensive patients with high cardiovascular risk and whose BP was uncontrolled by a suitable previous treatment. In our study we were able to illustrate a higher BP variability at the first visit compared with the 3 months visit. In addition we found an AASI reduction (which might reflect arterial rigidity). These rapid changes, observed in our study, might correlate with the results of the randomized, controlled ASCOT-BPLA study and are appropriate to predict the cardiovascular morbidity and mortality.